CALLUS INDUCTION AND PROPAGATION OF COCOA (Theobroma cacao L.) CLONES SULAWESI 2 IN VARIOUS CONCENTRATION OF 2,4-D, BAP ADDING WITH COCONUT WATER - Haliani,Wardah,I Nengah Suwastika (Tadulako University, 2015)
The goals of this experimen were to obtain the best concentration of 2,4-D with 15% coconut water to induced cacao callus, and the best concentration of BAP with 15% coconut water in callus propagation. This was experimental research which arranged by Completely Randomized Design, consists of two steps, callus induction and callus propagation. Callus induction from cacao flowers used several concentrations of 2,4-D combined with 15% of coconut water. In callus propagation, the medium treated by various concentrations of BAP with 15% of coconut water. This research was undertaken during period of time February until April 2016 at Laboratory of Forestry BiotecnologyForestry Faculty of Tadulako University. Data was analysed with analysis of variance and difference between treatment were determined by using BNJ at 5%. The result showed that the best medium for callus induction was 2.0 mg/L of 2,4-D with 15% of coconut water (K3). This medium produced callus in 13.50 days after induction with 99,17% of explants producing callus. Treatment of 2 mg/L of 2,4-D + 1.0 mg/L of BAP + 15 % of coconut water (SK6) was giving best response in callus propagation. This medium produced 0.55 ml volume of callus, white-yellowish callus with crumb textured which were active in cell proliferation.